Citation analysis of research field and information technology development - Sinha, Suresh; Dhiman, Anil K. (New Delhi : Ess Ess Publications, 2001)
General Collection
Keywords: Citation analysis; Information technology; Research field; Technology development; Building science; Library network; Bibliomatric